Gamification in the context of digital transformation of education - Anastasia G. Shirokolobova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper focuses on one of the urgent problems of modern education gamification in the context of digital transformation of education. The digital transformation of education has created not only the problem of changing the teaching system, but also has given great opportunities to teachers to use the synthesis of the best teaching traditions and introduction of digital technologies into the educational process, since digital technologies can change the form of teaching disciplines radically. A review of scientific literature on the issue under the study allowed us to conclude that gamification has been used in scientific publications mainly in three areas of knowledge: marketing, information management and education. The aim of the research is to develop a level-based gamification system for technical and humanitarian subjects, which can be the element of electronic courses on the LMS Moodle platform and allow to form and evaluate soft skills and increase the student motivation in the process of blended learning. The research methods were the analysis and generalization of methodological literature on the topic; observation methods (direct and indirect observation, questionnaire), experiment. The practical basis of the research was made up in the following subjects Foreign Language, Resistance of materials, Philosophy, Life Safety, History of Russia, Engineering Graphics. Electronic courses were developed for the implementation of blended learning in the educational process in the LMS Moodle platform at a technical university. The definition of the term gamification is considered. An experiment was conducted to develop an electronic course on the LMS Moodle platform with the introduction of gamification in the educational process. The author suggests a four-level gamification system integrated into e-courses, which allows to form and evaluate the formation of soft skills and increases motivation for learning.